2019
DOI: 10.1371/journal.pone.0215452
|View full text |Cite
|
Sign up to set email alerts
|

Array expression meta-analysis of cancer stem cell genes identifies upregulation of PODXL especially in DCC low expression meningiomas

Abstract: Background Meningiomas are the most common intracranial tumors, with a subset of cases bearing a progressive phenotype. The DCC netrin 1 receptor ( DCC ) is a candidate gene for early meningioma progression. Cancer stem cell (CSC) genes are emerging as cancer therapeutic targets, as their expression is frequently associated with aggressive tumor phenotypes. The main objective of the study was to identify deregulated CSC genes in meningiomas. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…It is overexpressed in various tumor cell types and is associated with their aggressiveness and poor prognosis ( Xu et al, 2018 ). PODXL upregulation is a cancer stem cell marker in meningiomas ( Schulten and Hussein, 2019 ) and a marker of poor outcome in patients with GBM ( Binder et al, 2013 ). It is proposed as a biomarker of poor prognosis in colorectal cancers also ( Larsson et al, 2012 , 2013 , 2016 ; Lee et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is overexpressed in various tumor cell types and is associated with their aggressiveness and poor prognosis ( Xu et al, 2018 ). PODXL upregulation is a cancer stem cell marker in meningiomas ( Schulten and Hussein, 2019 ) and a marker of poor outcome in patients with GBM ( Binder et al, 2013 ). It is proposed as a biomarker of poor prognosis in colorectal cancers also ( Larsson et al, 2012 , 2013 , 2016 ; Lee et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…GO analysis showed that shared hypermethylated genes in primary tumour and LNM were mainly related to synaptic and neural activity. Interestingly, these biological processes have been previously associated with CICs [ 43 , 44 ]. In addition, we found enrichment of other biological processes, including mesenchymal development, tissue morphogenesis and stem cell differentiation, which are known mechanisms for EMT and metastasis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to non-CSCs, CSCs are distinct for their immune resistance, and cancer immunosurveillance enhances certain populations of cancer cells with stem-like characteristics. For CSCs to maintain the tumorigenic process, CSC immune evasion is essential, including elevated PD-L1 expression [224,225]. In addition to immune evasion, CSCs display plasticity in terms of favorable DNA repair pathways in response to genotoxic-mediated DNA damage.…”
Section: Topo-active Drugs and Cscsmentioning
confidence: 99%
“…Standard cancer therapies often fail due to the generation of CSCs, with signaling pathways like Wnt, Hedgehog, Notch, hypoxia and PI3K/AKT/mTOR being aberrantly regulated in these cells [225][226][227]. These signaling pathways are also involved directly or indirectly with resistance to topo-active drugs in cancer cells [33].…”
Section: Topo-active Drugs and Cscsmentioning
confidence: 99%